Hydroxypropyl cellulose/TEMPO-산화 처리된 셀룰로오스나노섬유를 이용한 복합필름의 기계적 및 열적 특성 - 조유정; Yu Jeong Jo; 조혜정; Hye Jung Cho; 전상진; Sang Jin Chun; 이선영; Sun Young Lee (목재공학(Journal of the Korean Wood Science and Technology), 2015)
본 연구에서는 HPC (hydroxypropyl cellulose)와 TEMPO 산화된 셀룰로오스 나노섬유(Tempo-oxidized cellulose nanofibrils, TOCN)가 보강된 복합필름을 제조하였다. 복합필름의 기계적, 열적 특성을 관찰하기 위해 인장강도 및 열중량 분석기(TGA)를 측정하였다. HPC/TOCN 복합필름에서 TOCN의 함량이 1 wt%에서 5 wt%까지 증가할수록 인장강도와 인장탄성계수는 직선적으로 증가하는 경향을 보였다. 그러나 TGA 분석 결과, TOCN의 함량에 관계없이 HPC/TOCN 복합필름의 열 안정성은 거의 차이가 없었다. Hydroxypropyl cellulose (HPC) composite films filled with TEMPO-oxidized cellulose nanofibrils (TOCN) were prepared in this study. In order to investigate mechanical and thermal properties of HPC/TOCN composite films, tensile strength and thermogravimetric analysis (TGA) wer performed. As the loading level of TOCN increased, the tensile strength and modulus increased significantly. However, thermal stability of HPC/TOCN composite films was not related to the loading levels of the TOCN.